DOSE CALCULATION FOR THE HALF BLOCKED FIELDS DEFINED BY INDEPENDENT JAWS - SURIYAPEE, Sivalee; JUMPANGERN, Chotika; PUANGNAK, Chusak (The ASEAN Journal of Radiology, 2023)
A system of dose calculation of a 6 MV photon beam from a Clinac 1800 linear acce -lerator for the half blocked fields defined by independent jaws was designed. The dose is computed as the product of the field size factors, the off axis ratios and the percentage depth dose which are determined from a data set of symmetric fields. The dosimetric measurements of these parameters for asymmetric fields were performed to evaluate the calculation method. The field size factors for asymmetric fields are within 1.1% compared to those for symmetric fields corrected for off axis ratios. Asymmetric field percent depth doses differ from those of symmetric field with maximum of 7.5% for field sizes range 4x4 to 20x20 cm. and depth down to 20 cm. The measured isodose curves of asymmetric fields show about 4% reduction of dose near the field edge closed to the flattening filter center. Calculation of the doses for half beam by this method have been checked by the measurement of the dosage at 1.5, 5 and 10 cm depth, the result shows an agreement within 1.3% which is acceptable.